PENGARUH PENERAPAN SERVICE LEARNING TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XI SMA NEGERI 1 BOYOLALI TAHUN PELAJARAN 2011/2012 THE INFLUENCE OF SERVICE LEARNING TOWARD BIOLOGY LEARNING ACHIEVEMENT OF XI DEGREE STUDENTS AT SMA NEGERI 1 BOYOLALI IN ACA - Cahyani, Vita Anggun; Santosa, Slamet; Indrowati, Meti (Prosiding Seminar Biologi, 2012)
ABSTRACT   The aim of this research wants to know the influence of Service Learning strategy toward biology learning achievement of XI degree students at SMA Negeri 1 Boyolali in 2011/2012 academic year. This research was quasi experiment research which use posttest only control design. This research applyed Service Learning strategy in experimental group and conventional strategy with discussion, classical course and question-answer method in control group. Population?s research is the entire class XI IPA at SMA Negeri 1 Boyolali in 2011/2012 academic year.  Sampling techniques used cluster random sampling. Random result has chosen XI IPA 6 as experiment group and XI IPA 4 as control group.  Data was collected using questionnaire, multiple choice test, observation sheet, and document. The data were analyzed by t-test. The research concluded that the application of Service Learning strategy has taken good effect toward student?s achievement cognitive, psychomotor, and  affective domain in learning biology of SMA Negeri 1 Boyolali.   Keywords: Service Learning strategy, Biology Learning Achievement.